Polymer-vesicle association - Antunes, Filipe E. (2008)
Mixed polymer-surfactant systems have been intensively investigated in the last two decades, with the main focus on surfactant micelles as the surfactant aggregate in interaction. The main types of phase behavior, driving forces and structural/rheological effects at stake are now fairly well understood. Polymer-vesicle systems, on the other hand, have received comparatively less attention from a physico-chemical perspective. In this review, our main goal has been to bridge this gap, taking a broad approach to cover a field that is in clear expansion, in view of its multiple implications for colloid and biological sciences and in applied areas. We start by a general background on amphiphile self-assembly and phase separation phenomena in mixed polymer-surfactant solutions. We then address vesicle formation, properties and stability not only in classic lipids, but also in various other surfactant systems, among which catanionic vesicles are highlighted. Traditionally, lipid and surfactant vesicles have been studied separately, with little cross-information and comparison, giving duplication of physico-chemical interpretations. This situation has changed in more recent times. We then proceed to cover more in-depth the work done on different aspects of the associative behavior between vesicles (of different composition and type of stability) and different types of polymers, including polysaccharides, proteins and DNA. Thus, phase behavior features, effects of vesicle structure and stability, and the forces/mechanisms of vesicle-macromolecule interaction are addressed. Such association may generate gels with interesting rheological properties and high potential for applications. Finally, special focus is also given to DNA, a high charge polymer, and its interactions with surfactants, and vesicles, in particular, in the context of gene transfection studies